Pan-Cancer Analysis Reveals Disrupted Circadian Clock Associates With T Cell Exhaustion - Wu, Yingcheng; Tao, Baorui; Zhang, Tianyang; Fan, Yihui; Mao, Renfang (Frontiers in Immunology, 2019)
Although dysfunctional circadian clock emerged to be the hallmark of cancer, there remain fundamental gaps in our understanding of the underlying mechanisms. Here, we systematically analyzed the core genes of circadian clock (CLOCK, ARNTL, ARNTL2, NPAS2, NR1D1, NR1D2, CRY1, CRY2, RORA, RORB, RORC, PER1, PER2, and PER3) across a broad range of cancers. To our surprise, core negative regulators (PER1, PER2, PER3, CRY1 and CRY2) are consistently downregulated while core positive regulators show minimal alterations, indicating disrupted circadian clock in cancers. Such downregulation originates from copy number variations where heterozygous deletion predominates. The disrupted circadian clock is significantly associated with patients’ outcome. Further pathway enrichment analysis suggests that circadian clock widely impacts 45 pathways such as Ras signaling pathway and T cell receptor signaling pathway. By using state-of-the-art immune cell deconvolution and pathway quantification, we demonstrate that abnormal circadian clock contributes to T cell exhaustion and global upregulation of immune inhibitory molecules such as PD-L1 and CTLA-4. In summary, the rhythm of circadian clock in cancers is disrupted. Abnormal circadian clock linked with immune evasion may serve as a potential hallmark of cancer.